2018
DOI: 10.3389/fneur.2018.00121
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Bradykinesia and Rigidity in Parkinson’s Disease

Abstract: BackgroundIn the last decades, several studies showed that wearable sensors, used for assessing Parkinson’s disease (PD) motor symptoms and recording their fluctuations, could provide a quantitative and reliable tool for patient’s motor performance monitoring.ObjectiveThe aim of this study is to make a step forward the capability of quantitatively describing PD motor symptoms. The specific aims are: identify the most sensible place where to locate sensors to monitor PD bradykinesia and rigidity, and identify o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 21 publications
2
76
0
Order By: Relevance
“…These fluctuations are captured by both gyroscope and accelerometer sensors and seem to be detected similarly when using either sensor type alone. Bradykinesia is defined as slowness to voluntarily initiate movement, with decreasing speed and amplitude over time [23,24]. In addition, bradykinesia-focused items in the MDS-UPDRS generally have more subjective descriptions of different scores than tremor-focused items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fluctuations are captured by both gyroscope and accelerometer sensors and seem to be detected similarly when using either sensor type alone. Bradykinesia is defined as slowness to voluntarily initiate movement, with decreasing speed and amplitude over time [23,24]. In addition, bradykinesia-focused items in the MDS-UPDRS generally have more subjective descriptions of different scores than tremor-focused items.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that relative utility of data is highly dependent on body location and the intended application [22,34]. For instance, sensors collecting data from a distal limb location are most effective for identifying symptoms in that limb [24], whereas more proximal sensor locations may be helpful for monitoring gait and posture [35]. This study focused on motor symptoms of the upper limb using a flexible sensor on the hand, but other sensor placements may be relevant for monitoring global presentations of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The objective and standardized clinical evaluation of the motor signs of PD, especially for rigidity, is based on a semi-quantitative scoring system through clinical scales such as the Unified Parkinson's disease Rating Scale (UPDRS) [5]. However, even a neurologist with expertise in movement disorders can commit an error of up to 20% in the accuracy of the diagnosis [6]. In recent decades, objective methods have been developed to quantify muscle tone.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies such as portable sensors, which include inertial measuring units (IMUs) with accelerometers, gyroscopes, and magnetometers or potentiometers, offer systems that are non-invasive, trustworthy, quick, remote, economical, and objective [6]. Although they are not especially up-to-date (they were first used in this population in the 1990s) [6], their use has been recently included and extended in research and clinical environments for the evaluation of subjects with PD [10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Angeles et al used inertial motion, muscle activity and force sensors to measure both elbow and wrist rigidity to assess the impact of DBS therapy on the rigidity symptom [17]. Di Biase et al, on the other hand, measured elbow and wrist rigidity and their changes during DBS procedure, using magnetic-inertial wearable sensors [18]. More recently, Perera et al developed a new system to measure the rigidity of the metacarpophalangeal joint, consisting of a miniature motor to flex the third digit of the hand.…”
Section: Introductionmentioning
confidence: 99%